Premature Infants And Methods Of Care In Pediatric (Texas Journal of Medical Science, 2025)
Premature babies are those born before 37 weeks of gestation or with a birth weight of less than 2500 grams. This problem is relevant all over the world and has a serious impact on infant mortality and child health in many countries. According to statistics, millions of premature babies are born worldwide every year, and many of them have problems with survival or development, depending on the care conditions.